Lines of Activity Addressed to Families: Limiting the Participatory Approach as with Casework Practitioners - Kamińska-Jatczak, Izabela (Participatory Social Work: Research, Practice, Education, 2019)
The chapter shows the course of activity of family assistants – caseworkers situated in the field of child protection practice in Poland. The contribution undertakes a reflection on the constraints in the implementation of the participatory approach which is found in the process of activities performed by assistants. These constraints are related to the scale of the problems faced by family members, as well as the wider determinants of institutional and legislative issues that prescribe the formal framework for the activity of caseworkers. The chapter describes the types of participation of family assistants and users that show the real face of participation, located in the field of social work with families, in particular in relation to child protection practice.